EXPLORING SILENT HEART ATTACKS IN TYPE 2 DIABETES PATIENTS FACTORS INFLUENCING OCCURRENCE, BHAGALPUR: A CROSS-SECTIONAL STUDY AT HOSPITALS - Sinha, Anand; Bharty, Rolly (Student's Journal of Health Research Africa, 2024)
Background No chest pain or breathlessness characterizes silent myocardial infarctions (SMIs). These asymptomatic events are especially concerning for type 2 diabetics (T2DM), who are at higher risk for cardiovascular disease. The study investigated the prevalence and factors associated with silent myocardial infarction in asymptomatic Type 2 Diabetes Mellitus patients, focusing on abdominal obesity, glycemic control, and gender during treadmill testing. Methods The cross-sectional study included 35 asymptomatic T2DM patients aged 40-60 years, with no clinical evidence of coronary artery disease. Data collection involved detailed medical history, clinical examination, resting ECG, and laboratory investigations. Participants underwent treadmill testing, with the procedure stopped if symptoms occurred. Statistical analysis was done, with significance set at p < 0.05. Results The mean age of participants was 52.6 ± 6.8 years, with 51.4% being male. Abdominal obesity was present in 60% of the individuals. Symptoms such as chest pain or shortness of breath occurred in 22.9% during treadmill testing. A significant correlation was found between abdominal obesity and symptoms (p = 0.043), whereas gender was not significantly related (p = 0.321). Mean lab results showed: HbA1c 7.3% (± 0.8), FBS 155.2 mg/dL (± 40.6), and total cholesterol 210.5 mg/dL (± 45.9). No significant difference in mean HbA1c levels was found between symptomatic and asymptomatic subjects (p = 0.179). Conclusion The study highlights the significant prevalence of silent myocardial ischemia in asymptomatic T2DM individuals, with abdominal obesity being a notable risk factor for symptom occurrence during treadmill testing. Glycemic control, as indicated by HB1AC levels, did not show a direct influence on symptom presentation during exercise stress testing. Recommendations Regular screening for silent myocardial ischemia is suggested for asymptomatic T2DM patients, especially those with abdominal obesity. To prevent silent heart attacks in this high-risk population, weight control, and lifestyle changes should be prioritized.